STRATEGIC TALENT MANAGEMENT IN ISLAMIC ORGANIZATIONS: BUILDING WORKFORCE RESILIENCE AMID GLOBAL ECONOMIC PROTECTIONISM - Akbar Riskal Amani; Muhammad Zaky; Dudang Gojali; Iwan Setiawan; Kadar Nurjaman; Lilis Sulastri (Gunung Djati Conference Series, 2025)
This study investigates how Islamic organizations adopt strategic talent management (STM) approaches to build workforce resilience amid the resurgence of global economic protectionism. As protectionist policies reshape labor markets and restrict cross-border opportunities, organizations rooted in Islamic values face unique challenges in sustaining human capital competitiveness. Drawing upon a comprehensive literature review, this paper synthesizes findings from peer-reviewed journals and scholarly works published over the past decade. The review reveals that STM in Islamic contexts must align with core ethical principles such as Shura (consultation), Amanah (trust), and Ihsan (excellence). Resilience is fostered not only through skill development and succession planning but also through spiritual and cultural integration. The findings highlight the increasing relevance of adaptive leadership, inclusive organizational culture, and employee well-being strategies in uncertain economic environments. However, most existing literature fails to explore the intersection between Islamic organizational identity and strategic talent frameworks. This research fills that gap by offering an integrative conceptual analysis of STM in Islamic institutions under global economic stress. The paper concludes by proposing a research agenda for future empirical studies in faith-based organizational resilience. Ultimately, this work contributes to a broader understanding of talent strategy in navigating macroeconomic uncertainty through Islamic organizational perspectives.